Stress Dissipation Encoded Silk Fibroin Electrode for the Athlete‐Beneficial Silk Bioelectronics. Issue 8 (9th January 2022) - Choi, Woojin; Heo, Deokjae; Kim, Taeho; Jung, Sungwon; Choi, Moonhyun; Heo, Jiwoong; Kwon, Jae‐Sung; Kim, Byeong‐Su; Lee, Wonhwa; Koh, Won‐Gun; Cho, Jeong Ho; Lee, Sangmin; et al.
Abstract: The kinetic body motions have guided the core‐shell fabrics of wearable bioelectronics to be elastoplastic. However, the polymeric electrodes follow the trade‐off relationship between toughness and stretchability. To this end, the stress dissipation encoded silk fibroin electrode is proposed as the core electrode of wearable bioelectronics. Significantly, the high degree of intrinsic stress dissipation is realized via an amino acid crosslink. The canonical phenolic amino acid (i.e., tyrosine) of silk fibroin is engineered to bridge the secondary structures. A sufficient crosslink network is constructed when tyrosine is exposed near the amorphous strand. The stress dissipative tyrosine crosslink affords 12.5‐fold increments of toughness (4.72 to 58.9 MJ m −3 ) and implements the elastoplastic silk fibroin. The harmony of elastoplastic core electrodes with shell fabrics enables the wearable bioelectronics to employ mechanical performance (elastoplasticity of 750 MJ m −3 ) and stable electrical response. The proposed wearable is capable of assisting the effective workouts via triboelectricity. In principle, active mobility with suggested wearables potentially relieves muscular fatigues and severe injuries during daily fitness. Abstract : The stress dissipative network is encoded within the silk fibroin electrode via tyrosine crosslink. Since the phenol group of tyrosine links the secondary structures, the trade‐off relationship between toughness and stretchability has been overcome, meaning the realization of the elastoplasticity. Further, the elastoplastic silk fibroin electrode enables the energy harvesting wearables for the active athletes.